Efficacy and stability of pyridaben and endosulfan in a bioassay with whitefly Bemisia tabaci (Gennadius, 1889) biotype B (Hemiptera: Aleyrodidae). - Silva, Leonardo (2008)
The objective of this research was to obtain dose-mortality curves and verify the stability of pyridaben and endosulfan for Bemisia tabaci Biotype B adults, using the Bristol papers technique inside glass tubes. Initially, each insecticide was diluted in six concentrations varying from 50 to 800 mg of pyridaben/L of acetone and from 87.5 to 2450.0 mg of endosulfan / L of acetone. Other bioassay was prepared in only one concentration of 800 and 2450 mg of active ingredient (a.i.) of pyridaben and endosulfan, respectively, for each acetone liter. Bristol papers were dipped in each insecticide treatment. They were dried and introduced in a glass tube. Each one received about 120 adult whiteflies. After three hours insect mortality was recorded in each tube. We observed an increasing mortality of B. tabaci among the concentrations; and the maximum mortality was reached with 962,0 mg of pyridaben/L and with 2029, 0 mg of endosulfan/L. Pyridaben at 800 mg a.i./L and endosufan at 2450 mg a.i./L were stabilized over 12 days.